Capillary membrane-immobilised polyphenol oxidase and the bioremediation of industrial phenolic effluent - Edwards, Wade (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 1999)
Waste-generating industrialisation is intrinsically associated with population and economic proliferation. This places considerable emphasis on South Africa's water shortage due to the integral relationship between population growth rate and infrastructure development. Of the various types of industry-generated effluents, those containing organic pollutants such as phenols are generally difficult to remediate. Much work has been reported in the literature on the use of enzymes for the removal of phenols from these waste-streams but little application of this bioremediation approach has reached practical fruition. This study focuses on integrating and synergistically combining the advantages of enzyme-mediated dephenolisation of synthetic and industrial effluent with that of membrane teclmology. The ability of the enzyme polyphenol oxidase to convert phenol and a number of its derivatives to chemically reactive o-quinones has been reported extensively in the literature. These o-quinones can then physically be removed from solution using various precipitation or adsorption techniques. The enzyme is, however, plagued by a product-induced phenomenon known as suicide inactivation, which renders it inactive and thus limits its application as a bioremediation tool. Integrating membrane technology with the enzyme's catalytic ability by immobilising polyphenol oxidase onto polysulphone and poly(ether sulphone) capillary membranes enabled the physical removal of these inhibitory products from the micro-environment of the immobilised enzyme which therefore increased the phenol conversion capability of the immobilised biocatalyst. Under non-immobilised conditions it was found that when exposed to a mixture of various phenols the substrate preference of the enzyme is a function of the R-group. Under immobilised conditions, however, the substrate preference of the enzyme becomes a function of certain transport constraints imposed by the capillary membrane itself. Furthermore, by integrating a quinone-removal process in the enzyme-immobilised bioreactor configuration, a 21-fold increase in the amount of substrate converted per Unit enzyme was observed when compared to the conversion capacity of the inunobilised enzyme without the product removal step. Comparisons were also made using different membrane bioreactor configurations (orientating the capillaries transverse as opposed to parallel to the module axis) and different immobilisation matrices (poly(ether sulphone) and polysulphone capillary membranes). Conversion efficiencies as high as 77% were maintained for several hours using the combination of transverse-flow modules and novel polysulphone capillary membranes. It was therefore concluded that immobilisation of polyphenol oxidase on capillary membranes does indeed show considerable potential for future development.
Keywords: Membranes (Technology); Effluent quality; Pollutants; Phenols; Water -- Purification